2004
DOI: 10.7202/008299ar
|View full text |Cite
|
Sign up to set email alerts
|

Fabric, paleomagnetism, and interpretation of pre-illinoian diamictons and paleosols on Cloudy Ridge and Milk River Ridge, Alberta and Montana

Abstract: Pebble fabrics and sedimentological properties indicate that pre-Wisconsinan diamictons (Kennedy Drift) on Cloudy Ridge (Alberta) and Milk River Ridge (Montana) are of glacial rather than colluvial origin. S1 and S3 eigenvalues of the upper units on the two ridges are typical of undeformed lodgement till whereas those of the lower unit on Milk River Ridge are typical of glacigenic sediment flow. Other properties, including compact matrices, striations on stones, mean pebble dip angles, and Schmidt equal-area s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…The intensely weathered diamicton in some places possibly is nonglacial alluvium; in some other places possibly it is till or alluvium overlain by till. Two pebble fabric measurements indicated to Karlstrom (Karlstrom, 2000b;Karlstrom and Barendregt, 2001) that the sediment he sampled is till. His till 1, till 2, and till 3 have reversed remanent geomagnetic polarity (Cioppa and others, 1995).…”
Section: Outlet-glacier Piedmont Lobesmentioning
confidence: 98%
See 3 more Smart Citations
“…The intensely weathered diamicton in some places possibly is nonglacial alluvium; in some other places possibly it is till or alluvium overlain by till. Two pebble fabric measurements indicated to Karlstrom (Karlstrom, 2000b;Karlstrom and Barendregt, 2001) that the sediment he sampled is till. His till 1, till 2, and till 3 have reversed remanent geomagnetic polarity (Cioppa and others, 1995).…”
Section: Outlet-glacier Piedmont Lobesmentioning
confidence: 98%
“…The temporal relation of till 1 to the oxygen isotope record is problematic. Karlstrom and Barendregt (2001) indicated that till 4 has normal remanent polarity. However, according to Cioppa and others (1995), the buried soil in till 4 has normal polarity, but the polarity of till 4 was not determined.…”
Section: Outlet-glacier Piedmont Lobesmentioning
confidence: 99%
See 2 more Smart Citations
“…36 In that sense, macro-fabric analysis focusses on the visible features of the coarse fraction of the sediments. [37][38][39][40] This technique has been used in different kinds of sediments, mainly glacial, [41][42][43][44][45][46][47][48][49][50] periglacial [51][52][53] and slope 54,55 deposits. Macro-fabric analyses have been performed to distinguish between different types of deposits such as mudflows and till, 56 different types of slope deposits, 57 rock glaciers and other periglacial landforms such as protalus ramparts 58,59 or landslides, scree and moraines.…”
Section: Introductionmentioning
confidence: 99%